The Issues and Challenges of Hady from Different Islamic Schools of Thought - Jamiu, Fatai Owolabi (NIU Journal of Social Sciences, 2019)
Hady is the second most important obligatory annual rite for Muslim pilgrims from all over the world to perform during the fifth pillar of Islam, the pilgrimage in the city of MinÄ. There are divergent opinions among different schools of thought on how this aspect is carried out. Due to the improvement in the socio-economic and security related spheres, the number gradually increased. The paper discusses fundamental challenges with a view to finding possible solutions for better actualization of the hady . These challenges include: forgetfulness in observing the prescribed rules and regulations, accommodation for the multitudes of pilgrims in MinÄ, myriads of certified conditions for sacrificial animals, financial incapacitation for the purchase of a sacrificial animal, unreliable agent and fasting at Makkah. It is the view of this paper that if the identified challenges are properly addressed, there will be significant changes in offering at MinÄ. The paper revealed that different Islamic schools of thought agreed in the area of obligatory hady for a non-Makkan pilgrim but it is compulsory for a Makkan pilgrim performing á¸¤ajj al-Tamattuâ€˜ , they also agreed on its kinds, its requirements, its time, its non-obligatory for á¸¤ajj IfrÄd and fasting for á¸¤ajj pilgrim that cannot find the hady nor possess means to acquire one. They differed in its obligatory, its place, and distribution of its flesh. Keywords: Issues, Challenges, Hady , Islamic Schools, Thought